National, departmental and municipal rural agricultural land distribution in Colombia : analyzing the web of inequality, poverty and violence (2005)
Recent literature points to a relationship between inequality, economic growth and socio-economic variables. In order to continue to research the relationship between these factors and inequality in Colombia, it is essential to construct a precise measure of rural land distribution. This paper presents calculations of rural land size and land value Gini coefficients for Colombia at the national, departmental and municipal levels using approximately 2.5 million registries of plot level data supplied by the Instituto Geográfico Agustín Codazzi. In general, value Ginis, where value controls for land quality and improvements, are lower than plot size Ginis, and even after meticulous filtration anomalies remain in the data. Additionally, the relationship between the Gini coefficients and municipal level variables are analyzed to consider the relation between inequality, poverty, rurality and other municipal characteristics. Lastly, earlier results relating Gini to violence are reconsidered. After controlling for other factors, distribution does not explain significantly violence.